Phytochemical Analysis, Antioxidant and Anticancer Effects of Clitoria ternatae Extract on Breast T47D Cancer Cells - Arsianti, Ade; Mahindra, Shahjahan Pasha; Azizah, Norma Nur; Fajrin, Ajeng Megawati; Nadapdap, Lince Dameria (Indonesian Journal of Medical Chemistry and Bioinformatics, 2022)
Background: Breast cancer is one of the most common and deadly forms of cancer in the world. Cancer is a multi-factorial disease. Genetic factors, environment and lifestyle have a role in the development of cancer. One of the mechanisms of cancer development is when an imbalance between free radicals and antioxidants in the human body occurs. Uncontrolled and excessive amount of free radicals and cause cell damage and uncontrolled cell growth. Clitoria ternate is a plant that is often found in Asia and many of the benefits of this flower have been studied. This study aims to determine the phytochemical constituents, antioxidant activity, and cytotoxic activity of Clitoria ternatea against T47D breast cancer cells. Method: Clitoria ternatea in the form of dry powder is macerated in a multi-level manner with n-hexane, ethyl acetate, and ethanol as solvents, producing a Clitoria ternatea extract of the respective solvents. Each extract is then evaluated for its phytochemical constituents, antioxidant activity, and cytotoxic activity using phytochemical test, thin layer chromatography (TLC), DPPH assay, and MTT assay respectively. Results: Phytochemical analysis of Clitoria ternatea shows the presence of glycosides, flavonoids, tannins and triterpenoids with TLC revealing the presence of ten phytochemical constituents. DPPH assay reveals that Clitoria ternatea exhibits a very active antioxidant activity. MTT assay revels Clitoria ternatea has a high cytotoxic activity towards T47D breast cancer cell line with IC50 value ranging from 1.27 μg/mL to 32.38 μg/mL. Conclusion: Chemical constituents of Clitoria ternatea is responsible for the antioxidant and cytotoxic activity towards T47D breast cancer cell line.